SOSIALISASI DAN PENDAMPINGAN SERTIFIKASI HALAL PRODUK PELAKU USAHA MIKRO KECIL DAN MENENGAH (UMKM) KABUPATEN SUMBAWA NUSA TENGGARA BARAT - Muhammad Rafi’i Sanjani; Indah Fitriana Sari (LPPM ITB AAS Indonesia Surakarta, 2024)
This mentoring activity is to provide understanding and assistance about the importance of halal certification for processed products by providing knowledge and understanding of halal labels in the form of product certification, educating about the choice of ingredients used and forming experience on the steps to apply for halal certification through applications. With the addition of knowledge and experience about halal certification, it can provide benefits including increasing productivity, increasing consumer confidence, increasing market share and increasing business competitiveness for Micro, Small and Medium Enterprises (MSMEs) of Sumbawa Regency. In addition, it is also able to expand the scope of sales by having halal certification, MSME products will be more accepted in the market, especially among Muslim consumers who need halal products both in the local, domestic markets and do not rule out the possibility of international markets. Socialization and mentoring activities through a month-long certification safari to several sub-districts in Sumbawa Regency with its implementation at the Village Office. The understanding and socialization are carried out through the stages of education to MSME actors to assistance in registering halal product assurance certification for MSME actors engaged in culinary micro, small and medium scale enterprises. With the assistance of the halal certification process, all problems regarding how to administer halal certification that are considered difficult can be accompanied until the issuance of the certificate and become a role model for other MSME actors, especially Sumbawa Regency, West Nusa Tenggara.